2010
DOI: 10.1016/j.jmwh.2009.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Consultation, Referral, and Collaboration Between Midwives and Obstetricians: Lessons From New Zealand

Abstract: There has been substantial growth in the provision of midwifery-led models of care, yet little is known about the obstetric consultation and referral practices of these midwives or the quality of the collaboration between midwives and obstetricians. This study aimed to describe these processes as they are practised in New Zealand, where midwifery-led maternity care is the dominant model. A total population postal survey was conducted that included 649 New Zealand midwives who provided midwifery-led care in 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 30 publications
(58 reference statements)
2
34
0
1
Order By: Relevance
“…We searched for descriptions of different forms of collaboration between obstetric professionals in other countries, such as Canada, Australia, New Zealand and the United Kingdom [20][21][22][23][24][25]. There were a number of different approaches: shared care provided by midwives and obstetricians for low and/or high risk cases, a form of case management or community antenatal care combined with intrapartum care delivered by hospital-based professionals.…”
Section: Towards a Shared Care Model: First A Theoretical Frameworkmentioning
confidence: 99%
“…We searched for descriptions of different forms of collaboration between obstetric professionals in other countries, such as Canada, Australia, New Zealand and the United Kingdom [20][21][22][23][24][25]. There were a number of different approaches: shared care provided by midwives and obstetricians for low and/or high risk cases, a form of case management or community antenatal care combined with intrapartum care delivered by hospital-based professionals.…”
Section: Towards a Shared Care Model: First A Theoretical Frameworkmentioning
confidence: 99%
“…This is confirmed by 1,418 members of health and social services who took part in a cross-sectional study, giving leadership and formalised structures a lower ranking than interprofessional relational factors (Clancy et al, 2013). Working relationships between midwives and physicians are the subject of other studies (Murray-Davis et al, 2011;Pollard, 2011;Skinner & Foureur, 2010). In a quantitative survey (Skinner & Foureur, 2010), midwives rated these as being excellent, but a qualitative study indicated that midwives experience their working relationships to physicians diversely (Pollard, 2011).…”
Section: Relationshipsmentioning
confidence: 93%
“…Midwives participated exclusively in five of the studies (Ayerle et al, 2014;Fontein-Kuipers, Budé, Ausems, Vries, & Nieuwenhuijze, 2014;Murray-Davis, Marshall, & Gordon, 2011;Nagel-Brotzler et al, 2005;Skinner & Foureur, 2010), of which one had a qualitative design (Murray-Davis et al, 2011). The populations of all the other studies were of varying composition, consisting midwives, nurses, physicians, associated health professionals, addressees of the care system, professional groups from social services, representatives of administration and politics, as well as members of other professions.…”
Section: Populations Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations